Analysis of Good Corporate Governance and Risk of Money Laundering: Terrorism Financing (ML/TF) at Securities Crowdfunding (SCF) in Indonesia - Bandono, Bayu; Setijanto, A. Dewo (Otoritas Jasa Keuangan, 2025)
We conducted a qualitative analysis method based on the results of a survey on governance and Anti-Money Laundering – Counter-Terrorism Financing (AML-CFT) addressed to each company implementing the SCF. In order to find out to what extent the implementation of governance and AML-CFT has been implemented by the SCF organizing companies, the questions in this research questionnaire are based on several aspects of governance and AML-CFT. This study analyzes the implementation of governance by SCF to find out and evaluate the extent to which the SCF companies are prepared to support a sustainable SCF industry, and the readiness to adequate infrastructure, including the Technical Guidelines for the Implementation of AML-CFT. Based on the survey results from 10 aspects of corporate governance, not all SCF implement good corporate governance. Furthermore, AML CFT implementation to prevent ML/FT risks also has not been fully carried out by SCF.